STRATEGI KOMUNIKASI DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI DAN UKM DALAM MELAKUKAN PEMBINAAN USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN KEPULAUAN MERANTI - Wahidah, Resti; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on the data obtained from Department of Industry, Trade, Cooperative and SMEs, there was a lot of MSMEs operating in Meranti Islands with different types of business listed on which managed natural resources in Meranti Island. That necessary for specific guidance in order to MSMEs is able to develop and survive in current global competition. The purpose of the research is to find out communication strategy in determining the audiences, the selection of media, deliver of message, and determine the communicator by Department of Industry, Trade, Cooperative and SMEs in Meranti Islands.The method used is qualitative description narrated descriptively. The informan in this research are Head of Department industry, Trade, Cooperative and SMEs, Head of Cooperative and SMEs, Head of Developments of MSMEs, Owners of coffee business, Owners of Sago business, and owner of weaving business. Data collection techniques used observation, interviews, and documentation.The result showed that communication strategy in MSMEs development regard to four factors that is the audience, media, message, and communicator. Strategy in determining the audience is to perform data collection of MSMEs then selected accordance the criteria to be include in coacing thedevelopment program. Media used are, media of group, printed media, and online media to communicate the information and knowledge to business owners. Then strategy in determining the communicator is the people who have knowledge of SMEs and selected according to the experienced and expertised.Keywords : Development, MSMEs, Communication Strategy